Coral reef degradation affects the potential for reef recovery after disturbance. (November 2018) - Roth, F.; Saalmann, F.; Thomson, T.; Coker, D.J.; Villalobos, R.; Jones, B.H.; Wild, C.; Carvalho, S.
Abstract: The loss of coral cover is often accompanied by an increase of benthic algae, a decline in biodiversity and habitat complexity. However, it remains unclear how surrounding communities influence the trajectories of re-colonization between pulse disturbance events. Over a 12-month field experiment in the central Red Sea, we examined how healthy (hard-coral dominated) and degraded (algae-dominated) reef areas influence recruitment and succession patterns of benthic reef foundation communities on bare substrates. Crustose coralline algae and other calcifiers were important colonizers in the healthy reef area, promoting the accumulation of inorganic carbon. Contrary, substrates in the degraded area were predominantly colonized by turf algae, lowering the accumulation of inorganic carbon by 178%. While coral larvae settlement similarly occurred in both habitats, degraded areas showed 50% fewer recruits. Our findings suggest that in degraded reefs the replenishment of adult coral populations is reduced due to recruitment inhibition through limited habitat complexity and grazing pressure, thereby restraining reef recovery. Highlights: We assessed impacts of coral-algal phase shifts on trajectories of re-colonization. Turf algae were the main colonizers on bare substrates in degraded areas. Algae suppress the accumulation of inorganic carbon, limiting reef cementation. Habitat degradation reduces post-settlement survival of coral larvae. Coral-algal phase shifts may limit coral reefs to recover after disturbance.